2020
DOI: 10.1002/cphc.201901076
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Competition between Hydrogen and Tetrel Bonds by a Magnesium Bond

Abstract: A computational study of the complexes formed by TF 3 OH (T=C, Si, Ge) with three nitrogen-containing bases NCH, NH 3 , and imidazole (IM) is carried out at the MP2/aug-cc-pVTZ level. TF 3 OH can participate in two different types of noncovalent interactions: a hydrogen bond (HB) involving the hydroxyl proton and a tetrel bond (TB) with the tetel atom T. The strength of the HB is largely unaffected by the identity of T while the TB is enhanced as T grows larger. The HB is preferred over the TB for most systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…As work has progressed, there has been recognition of π-holes as providing a means by which an aerogen bond (involving rare gas atoms) can form [100][101][102][103][104]. Other newly introduced types of σ/π-hole directed interactions are alkali and alkaline earth bond (e.g., beryllium bond, magnesium bond) in which atoms of 1st and 2nd groups contribute [105][106][107][108][109] or regium and spodium bonds which employ transition metals from 11th (regium [110][111][112][113][114][115]) or 12th (spodium [105,[116][117][118][119]) groups of the periodic table. The full range of these sorts of bonds, along with their designations, is summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…As work has progressed, there has been recognition of π-holes as providing a means by which an aerogen bond (involving rare gas atoms) can form [100][101][102][103][104]. Other newly introduced types of σ/π-hole directed interactions are alkali and alkaline earth bond (e.g., beryllium bond, magnesium bond) in which atoms of 1st and 2nd groups contribute [105][106][107][108][109] or regium and spodium bonds which employ transition metals from 11th (regium [110][111][112][113][114][115]) or 12th (spodium [105,[116][117][118][119]) groups of the periodic table. The full range of these sorts of bonds, along with their designations, is summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…As prominent examples, the appearance of tin and lead as building blocks for MOF's and other supramolecular synthons [10d] or the common layout of the germanium/tin nucleophile site interactions [10m,p] offer a good deal of promise for future development. The tetrel bond was also recently studied with regard to its contribution to anion recognition activity [11] and competition or cooperation with such other noncovalent interactions as hydrogen or halogen bonds [8c,12] . The π‐hole subgenre of the tetrel bond where the Lewis base line of attack is perpendicular to the plane of the tetrel‐containing molecule has been investigated as well [13] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cooperativity, either positive (synergy) or negative (anti‐synergy) is a very important phenomenon in many areas of chemistry 53–64 . Recently, Kukushkin and coworkers 57–64 have observed the existence of noncovalent interactions (hydrogen/halogen/chalcogen/π‐hole bonds) by X‐ray diffraction, investigated the cooperativity between them theoretically by DFT calculations followed by QTAIM analysis, and confirmed experimentally by combined FTIR, HRESI‐MS, 1 H NMR, and diffusion coefficient NMR measurements.…”
Section: Resultsmentioning
confidence: 94%